Surgical management of cholangiocarcinoma: case report (Basic Health sciencies journal, 2024)
Introduction: Cholangiocarcinoma is a malignant tumor originating in the epithelium of the intra- or extrahepatic bile ducts, rare and represents less than 2% of malignant tumors, its incidence is 1 or 2 new cases per 100,000 inhabitants each year, the techniques of hepatectomies have evolved over time, supported by the development of surgical instruments and vascular clamping methods. Clinical case: 28-year-old female patient with a history of cholelithiasis with a space-occupying lesion at the level of the bile duct and a previous failed diagnostic procedure, who presented extrahepatic bile duct narrowing at the level of the proximal common liver, compromising the bifurcation and right hepatic origin. tumor. (Bismuth IIIa) with secondary obstruction, lymphadenopathy with a reactive appearance in the hepatic hilum, so hepatectomy was performed with the described technique. Conclusions: The surgical treatment of planned hepatectomy helps to achieve a better balance between achieving radical tumor resection of hilar cholangiocarcinoma and reasonable control of the extent of surgical damage, however it requires greater arterial reconstruction, which is technically demanding and must be performed by For experienced surgeons, the selection of the surgical strategy should be based not only on the location of the tumor (Bismuth classification) but also on vascular involvement and future liver remnant.
Keywords: Cholangiocarcinoma; Hepatectomy; surgery; oncology